Capital Flows and Central Banking : The Indian Experience - Gupta, Poonam (World Bank, Washington, DC, 2016)
Because of the steady liberalization of the capital account since the early 1990s and increased financial integration of the Indian economy, capital flows to India have moved in tandem with broad global trends. This paper looks at the extent to which India’s monetary policy has been affected by the ebbs and flows of the capital it receives. For ease of narration, the paper divides the post-liberalization period since the early 1990s into three phases--early 1990s to early 2000s, a period of increasing but still modest capital flows; early 2000s to 2007-08, a period of capital flow surge when inflows increased rapidly; and a period of sudden stops and volatility, starting in 2008-09, when capital flows reversed in the post-Lehman Brothers collapse, and again during the tapering tantrum of 2013. The paper shows that although ordinarily domestic policy imperatives, such as price stability and growth, have taken precedence over issues related to exchange rate or capital flows in policy rate setting, some accommodation in money supply is evident during the surge and stop episodes. The broad policy mix to handle large increases or reversals of capital flows has included reserve management, liquidity management, and capital flow measures.